Geospatially explicit technoeconomic assessment of sustainable aviation fuel production: A regional case study in Virginia - Curtis D. Davis; Shravan Sreekumar; Richard Altman; Andres F. Clarens; James H. Lambert; Lisa M. Colosi (Fuel Communications, 2024)
There is strong interest in sustainable aviation fuels (SAF) to decarbonize aviation; however, local decision-makers will need to consider what additional incentives could stimulate SAF commercialization within their own jurisdictions. This study analyzed SAF production in Virginia, evaluating two biomass-to-energy platforms (gasification Fischer Tropsch [GFT] and pyrolysis) and two regionally abundant feedstocks (woody wastes and municipal solid wastes). A suite of open-access modeling tools were applied to possible SAF supply chains encompassing feedstock collection and transportation, conversion, and fuel upgrading and transport. Key modeling outputs were minimum product selling price (MPSP) ($/gallon) and life-cycle global warming potential (GWP) (g CO2eq/MJ). Results suggest that early SAF production via GFT will require local incentives of approximately $3.61 per gallon compared to $0.75 per gallon for pilot-scale pyrolysis. Location of production facility (by county) influences economic and environmental metrics but is not nearly as important as facility size (tonnes/year). Different formats of financial incentives (i.e., tax credits, loan forgiveness, etc.) offer markedly different reductions in SAF MPSP. Finally, under current federal incentives in the US, it is still more economically efficient to use pyrolysis (with higher GWP) than GFT (with lower GWP). Therefore, regional stakeholders will need to navigate the tradeoff between economic and environmental performances of these platforms. Though Virginia was used as a case study, the methodology is replicable for other jurisdictions, insofar it can be adapted for use in other locations without decision-makers having to completely build their own TEA models.